208k views
6 votes
First responder gets

First responder gets-example-1
First responder gets-example-1
First responder gets-example-2
User Gelo
by
6.6k points

1 Answer

8 votes

Explanation:

Storage facility => 12x²y³ • 4x⁴y²

Storage facility => 48x⁶y⁵


\implies \: \frac{12 {x}^(6) {y}^( - 4) z {}^(2) }{3x {}^(2) {y}^( - 6) z {}^(3) } \\ \implies \: 4( {x}^(6 - 2) ) * ({y}^( -4 + 6) ) *( {z}^(2 - 3) ) \\ \implies \: 4 {x}^(4) * {y}^(2) * {z}^(-1) \\ \implies \: \frac{4 {x}^(4) {y}^(2)}{z}

User Justadampaul
by
5.9k points